The impact of corporate governance and political connectedness on the financial performance of lebanese banks during the financial crisis of 2019-2021 - Hani El-Chaarani; Rebecca Abraham (Journal of Risk and Financial Management, 2022)
The Lebanese banking sector has become risky due to political and economic crises. At such times, corporate governance mechanisms ensure objectivity of assessment and rationality in decision making. We examine the impact of internal corporate governance mechanisms on the performance of Lebanese banks, with political involvement in the administration and ownership of the banks. We used linear regression on a sample of 194 bank-year observations from 2016 to 2021. The presence of independent members on boards of directors, and ownership concentration due to family ownership, had positive effects on bank return on assets, return on equity, liquidity levels, and loans issued. Efficient control, along with the presence of audit, and compliance committees reduced risk by increasing capital adequacy and reducing non-performing loans. Both administrative political connections and ownership political connections increased return on assets, increased return on equity, increased liquidity levels, and increased loans to deposits, while increasing non-performing loans. Agency conflicts suggest that granting loans due to political pressure increased non-performing loans.
Keywords: 650; corporate governance; agency conflicts; bank performance; political intervention